Technology solder of chrome canning tin - Гірін, О. Б.; Захаров, І. Д.; Овчаренко, В. І. (Eastern-European Journal of Enterprise Technologies, 2009)
The technology of electro chrome soldering tin by tin solder is made. The basis of the technology is developed flux mixed with "UP-Fs-2" application is for chrome tin soldering allowed to increase the coefficient of solder spread to 2,6-3,0 (at a rate not less than 1.0 standard)